Prevention of vitamin D deficiency in children following cardiac surgery: study protocol for a randomized controlled trial. Issue 1 (December 2015) - McNally, J.; O'Hearn, Katie; Lawson, Margaret; Maharajh, Gyaandeo; Geier, Pavel; Weiler, Hope; Redpath, Stephanie; McIntyre, Lauralyn; Fergusson, Dean; Menon, Kusum
Abstract Background Vitamin D is a pleiotropic hormone important for the recovery of organ systems after critical illness. Recent observational studies have suggested that three out of every four children are vitamin D deficient following cardiac surgery, with inadequate preoperative intake and surgical losses playing important contributory roles. Observed associations between postoperative levels, cardiovascular dysfunction and clinical course suggest that perioperative optimization of vitamin D status could improve outcome. With this two-arm, parallel, double blind, randomized controlled trial (RCT), we aim to compare immediate postoperative vitamin D status in children requiring cardiopulmonary bypass for congenital heart disease who receive preoperative daily high dose vitamin D supplementation (high-dose arm) with those who receive usual intake (low-dose arm). Methods/Design Eligibility requirements include age (>36 weeks, <18 years) and a congenital heart defect requiring cardiopulmonary bypass surgical correction. Enrollment of 62 participants will take place at a single Canadian tertiary care center over a period of 2 years. Children randomized to the high-dose group will receive age-based dosing that was informed by the Institute of Medicine (IOM) daily tolerable upper intake level (<1 year old = 1, 600 IU/day, >1 year old = 2, 400 IU/day). Children in the low-dose arm will receive usual care based on IOM recommendations (<1 year old = 400 IU, >1 year old = 600 IU). The primary outcome measure is immediate postoperative vitamin D status, using blood 25(OH)D. Discussion Maintaining adequate postoperative vitamin D levels following surgery could represent an effective therapy to speed recovery following CHD surgery. The proposed research project will determine whether preoperative supplementation with a dosing regimen based on the IOM recommended daily upper tolerable intake will prevent postoperative vitamin-D deficiency in the majority of children. The results will then be used to inform the design of a large international RCT exploring whether preoperative optimization of vitamin D status might improve short and long-term outcomes in this vulnerable population. Trial Registration Clinicaltrials.gov Identifier -NCT01838447 Date of registration: 11 April 2013